The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5217/ir.2016.14.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day mortality after percutaneous gastrostomy by endoscopic versus radiologic placement: a systematic review and meta-analysis

Abstract: Background/AimsA percutaneous gastrostomy can be placed either endoscopically (percutaneous endoscopic gastrostomy, PEG) or radiologically (radiologically-inserted gastrostomy, RIG). However, there is no consistent evidence of the safety and efficacy of PEG compared to RIG. Recently, 30-day mortality has become considered as the most important surrogate index for evaluating the safety and efficacy of percutaneous gastrostomy. The aim of this meta-analysis was to compare the 30-day mortality rates between PEG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…There are many studies reporting the efficacy and safety of PEG and RIG. However, the optimal technique for gastrostomy in individuals who have swallowing disturbances or PD remains unknown . A recent Cochrane meta‐analysis evaluating the safety and efficacy of these 2 techniques concluded that current evidence is insufficient to recommend 1 over the other …”
Section: Discussionmentioning
confidence: 99%
“…There are many studies reporting the efficacy and safety of PEG and RIG. However, the optimal technique for gastrostomy in individuals who have swallowing disturbances or PD remains unknown . A recent Cochrane meta‐analysis evaluating the safety and efficacy of these 2 techniques concluded that current evidence is insufficient to recommend 1 over the other …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although no endoscopy is necessary, RIG usually requires the passage of an NGT, which may be impossible in some cancer patients. Furthermore, few radiology teams seem to have acquired extensive experience with this technique [44][45][46][47][48].…”
Section: 21 Radiologically Inserted Gastrostomymentioning
confidence: 99%
“…[8][9][10][11] However, much of the current literature on fluoroscopic gastrostomy, in particular, has been limited to being outside of the United States or performed in a single institution or region. 7,8,[12][13][14][15][16][17][18][19] This study aims to evaluate the complication rates associated fluoroscopically placed gastrostomy tubes nationally in patients covered by Medicare parts A and B in the United States.…”
Section: Introductionmentioning
confidence: 99%